The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/nan.0b013e31824d289f
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Impact of Health Care

Abstract: Health care provision is a dangerous business. Health professionals recognize the potential for miscommunication, medication errors, and other possible threats to patient safety. Less evident are the hazards to the environment inherent in the everyday practice of patient care. This article addresses 3 areas of practice in which infusion nurses can make a positive impact on the environment: preferable intravenous (IV) supply purchasing, proper management of electronic equipment (including purchasing, servicing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In fact, this perspective has already supported the integration of climate content into nursing curricula (Leffers, McDermott-Levy, Nicholas, & Sweeney, 2017). Furthermore, a planetary health perspective would encourage nurse researchers to continue to develop this field and to study climate change's implications on the nursing profession, as well as the role nursing plays in advocating for a healthy climate (Barnes et al, 2010;Goodman, 2013;Leffers & Butterfield, 2018;Leffers et al, 2017;Lilienfeld, Nicholas, Breakey, & Corless, 2018;Lipkin, 2012;Sattler & Davis, 2007;Sayre et al, 2010). Finally, it would offer a framework for change in nursing practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this perspective has already supported the integration of climate content into nursing curricula (Leffers, McDermott-Levy, Nicholas, & Sweeney, 2017). Furthermore, a planetary health perspective would encourage nurse researchers to continue to develop this field and to study climate change's implications on the nursing profession, as well as the role nursing plays in advocating for a healthy climate (Barnes et al, 2010;Goodman, 2013;Leffers & Butterfield, 2018;Leffers et al, 2017;Lilienfeld, Nicholas, Breakey, & Corless, 2018;Lipkin, 2012;Sattler & Davis, 2007;Sayre et al, 2010). Finally, it would offer a framework for change in nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…This review identified 55 publications between 1995 and 2000, 96 publications between 2001 and 2005, 170 publications between 2006 and 2010, and 227 publications between 2011 and 2015 (Polivka & Chaudry, 2017). It is clear that nursing responded to the call put out by the National Academy of Medicine and has since developed some scholarship, education and practice in the area of environmental health (Álvarez-Nieto et al, 2018;Leffers & Butterfield, 2018;Lipkin, 2012;Sayre, Rhazi, Carpenter, & Hughes, 2010); however, the initial response was slow and the area is still far from being saturated.…”
Section: N Ur S Ing ' S Del Ayed Re S P On S Ementioning
confidence: 99%
“…Interior design plays a crucial role in the process of treatment and recovery of patients in health centers. The results show that healthcare environments influence people's physical and mental health, the treatment process and patients' recovery (Agom et al 2022;Bernhardt et al 2021;Elf et al 2020;Huisman et al 2012); Evidence on the healing role of hospitals also shows that environmental factors improve patient and staff performance through clinical practices (Lukasik et al 2022;Brambilla et al 2020;Konstantzos, 2020;Fadda, 2019;Laursen et al 2014;Lipkin, 2012). light and color are considered environmental features that have been shown to have a positive impact on the health of hospital patients (Kakitsuba, 2020;Leccese et al 2017;Kakitsuba, 2015;Hassan et al 2020;Boubekri, 2014;Rikard, 2006).…”
Section: Introductionmentioning
confidence: 98%